Square sugars: challenges and synthetic strategies. Issue 18 (31st March 2017) - Hazelard, Damien; Compain, Philippe
Abstract : The synthesis of square sugars requires innovative strategies based on efficient stereoselective methodologies, from organocatalysis to metal carbene insertion. Abstract : Square sugars (4-membered ring carbohydrate mimetics) are at the intersection of several important topics concerning the recent emergence, in medicinal chemistry, of glycomimetic drugs and small ring systems. Monosaccharide mimetics containing oxetane, azetidine, thiethane or cyclobutane rings present a number of synthetic challenges that are a powerful driving force for innovation in organic synthesis. In addition to the inherent issues associated with 4-membered rings, the high density of functional groups and asymmetric centres found in glycomimetics further complicates the matter and requires efficient stereoselective methodologies. The purpose of this review is to present an overview of the elegant strategies that have been developed to synthesize the different types of square sugars.